Political Ethics In Franz Magnis Suseno View And Relevance With The Indonesian Context - Wahyu Trisno Aji; Zakaria Ansori (Journal of Politica Governo, 2024)
This research aims to investigate the central role of political ethics in the views of Franz Magnis Suseno in shaping the identity and welfare of Indonesian society. Political ethics is considered a vital code of behavior to direct the attitudes and behavior of state administrators and political elites so that they are in line with the vision, mission and goals of state power. Without the presence of political ethics, justice, prosperity and the highest happiness of society are difficult to realize. This research uses a contextual-interpretative approach to describe and interpret data as text, linking real situations with theoretical meaning. The method used is literature study with a focus on the work of Franz Magnis Suseno as a primary source. Data sources involve books. The research results show that political ethics plays a crucial role in shaping the identity and welfare of Indonesian society. The concept of Bhinneka Tunggal Ika is the basis for uniting people in diversity, with the hope that they will be able to respect differences and build unity. Mutual respect in diversity is considered a basic ethical basis for Indonesian citizens. The main focus is to achieve community welfare by encouraging political participation to improve living conditions together. Political ethics, as a moral guideline, is recognized as crucial in facing political challenges and corruption in Indonesia. Pancasila values are considered the main guide to achieving the goals of social justice and prosperity. Franz Magnis Suseno's ideas about political ethics and the importance of Pancasila Moral Education (PMP) are a strong foundation for building a just, democratic and socially just society, in line with the principles of Pancasila as Indonesia's national identity.